How temporary is temporary ileostomy: variables delaying reversal of an ileostomy - F. Airani, Afroz Khan; Bhat, Chitra Y.; S. V., Bharat; Rodrigues, Gabriel (International Surgery Journal, 2018)
Background: Temporary diversion ileostomy are done to protect distal bowel anastomosis giving adequate time for the bowel repair to heal. Here we studied the reversal time for different temporary ileostomy done and found the factors causing delay in reversal of ileostomy. Methods: In a retrospective cohort of patients, data was collected from the MRD and the operating registry of department of general surgery from January 2013 to December 2017. Parameters like reversal time interval between creation to closure, type of ileostomy, timing of stoma creation, ostomy created with primary index surgery or subsequently, primary etiology that led to creation of ileostomy, ileostomy done on elective list or as an emergency and postoperative complications like anastomotic leak, surgical site infection, intra-abdominal collection were recorded. Results: Of 107 cases, 3 were planned permanent ileostomy and 2 lost follow up. About 77 underwent reversal with mean reversal time of 74.47days, 25 (24.50%) were nonreversed. 51 underwent ileostomy during their second surgical procedure (secondary stoma). End ileostomy, adjuvant chemotherapy, intra-abdominal collection and a secondary stoma caused a delay in the reversal of ileostomy. Conclusions: Although it is said that temporary ileostomies are reversed within 6 to 12weeks time, but reversal time is considerably delayed as what would be anticipated. Ileostomy carries considerable morbidity and psychological impact on lifestyle of patient. Non-reversal of ileostomy should be an important part of pre-procedural counselling because considerable number of ostomies may not be reversed which were deemed to be temporary initially.